2020
DOI: 10.1038/s41598-020-75439-1
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral dopamine neurotrophic factor (CDNF) protects against quinolinic acid-induced toxicity in in vitro and in vivo models of Huntington’s disease

Abstract: Huntington’s disease (HD) is a neurodegenerative disorder with a progressive loss of medium spiny neurons in the striatum and aggregation of mutant huntingtin in the striatal and cortical neurons. Currently, there are no rational therapies for the treatment of the disease. Cerebral dopamine neurotrophic factor (CDNF) is an endoplasmic reticulum (ER) located protein with neurotrophic factor (NTF) properties, protecting and restoring the function of dopaminergic neurons in animal models of PD more effectively th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…CDNF was also shown to have beneficial effects in animal models of Alzheimer’s disease [ 120 ], amyotrophic lateral sclerosis [ 121 ], and Huntington’s disease [ 122 ]. However, further studies are required to confirm these exciting results.…”
Section: Introductionmentioning
confidence: 99%
“…CDNF was also shown to have beneficial effects in animal models of Alzheimer’s disease [ 120 ], amyotrophic lateral sclerosis [ 121 ], and Huntington’s disease [ 122 ]. However, further studies are required to confirm these exciting results.…”
Section: Introductionmentioning
confidence: 99%
“…Quinolinic acid neurotoxicity is also thought to play a role in the further pathogenesis of Parkinson’s disease [ 66 ]. Thus, studies have shown that quinolinic acid or its Fe-chelate is involved in degeneration of the dopaminergic neurons in the substantia nigra (SN) of Parkinson’s disease patients [ 67 ]. SN degeneration combined with iron deposition is one of the key characteristics of this disease [ 68 , 69 ].…”
Section: Quinolinic Acidmentioning
confidence: 99%
“…The diffusion of CDNF in brain is more prolonged and distributed widely than that of other NTFs, and the half-life is approximately 5.5 h 23 , 36 , 37 . Previous studies have demonstrated that CDNF exerts neuroprotective and neurorestorative effects in rodent and non-human primate models of PD 27 , 37 39 .…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we demonstrated that a single intrastriatal injection of CDNF has a positive effect in the quinolinic acid (QA)-toxin model of HD 23 . CDNF improved motor behavior and increased the NeuN- and doublecortin-immunopositive cell populations in vivo and protected striatal neurons after QA toxin-induced cell death in vitro.…”
Section: Introductionmentioning
confidence: 99%